Water and Electricity Consumption and Carbon Footprint of Washing Machines - Filip Nastić; Dušan Gordić; Davor Končalović; Vladimir Vukašinović; Jelena Nikolić; Nebojša Jurišević (Energija, Ekonomija, Ekologija)
Considering the relatively high share of households in global final energy and water consumption, washing machines are home appliances with a significant potential for electricity and water saving. The potential depends on the energy rating of a washing machine and the consumption habits of consumers in a household. Therefore, a survey was conducted to determine the laundry habits of domestic consumers and the characteristics of their washing machines. Considering collected information, the annual consumption of water and electrical energy and carbon footprint caused by the use of washing machines can be estimated and compared with the rest of the world. It was concluded that laundry washing causes around 10% and 4% of total water and energy consumption in the Republic of Serbia, respectively, with a carbon footprint of 423.33 ktCO2.